THE SYSTEM OF BACHELOR STUDENTS’ ECOLOGICAL COMPETENCY FORMING IN HUMANITARIAN DIRECTIONS AND OF TEACHING - Valentin N. Mikhelkevich; Elena N. Chekanushkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article there are presented theoretic and methodology basis of projecting and practical realization of ecological competency of bachelor students of humanitarian directions and profiles of teaching. Here there are considered the main principles of foundation an information-didactic base of ecological competency forming due to the ecologization of humanitarian social ecological and natural science cycles, and also to the formation on their base of interdisciplinary didactic systems. There is presented the structural scheme of correlations between the interdisciplinary didactic systems, which are based on ecologized disciplines of humanitarian, social ecological and natural science cycles. There is considered the content and the structure of educational discipline “Connections with the society in the field of ecology”. There is given a model of students’ ecological competency system formation in the process of studying and mastering by them of “Connections with the society in the field of ecology” educational discipline.